Kebebasan Berekspresi Laki-Laki pada Media Sosial melalui Fashion Androgini - Pramesthi, Hanum Kanthi; Arista, Altabella Septi; Swastika, Hanif (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
For centuries, fashion has been a visual marker of our gender, and nowadays the term androgynous fashion has arisen. Being outside the binary, individuals in Indonesia dressing in this style often face discrimination due to its strong patriarchal culture. Consequently, Instagram has become a prominent platform for people to express themselves in a more intimate way. Utilizing the case study research method, Jovi Adhiguna Hunter, an androgynous fashion influencer, was chosen as the research object. His self-disclosure through fashion is analyzed using social penetration theory, with an emphasis on his Instagram posts @joviadhiguna from 2019 to June 2023. Previous studies have primarily examined the presence of androgynous individuals on social media and their personal branding. Therefore, this study aims to delve deeper into how Jovi Adhiguna discloses his identity through androgynous fashion. Employing qualitative research and a case study approach within the constructivism paradigm, the study finds that Jovi Adhiguna's Instagram self-disclosure has reached a stable stage.His consistent disclosures are accompanied by captions expressing Jovi Adhiguna Hunter's views on genderless design and are reflected in his choice of outfits, accessories, photo expression, and poses that embrace a feminine aesthetic, which has happened since 2021.